2023
DOI: 10.7554/elife.82283
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of human mitofusin-2-related lipodystrophy exhibits adipose-specific mitochondrial stress and reduced leptin secretion

Abstract: Mitochondrial dysfunction has been reported in obesity and insulin resistance, but primary genetic mitochondrial dysfunction is generally not associated with these, arguing against a straightforward causal relationship. A rare exception, recently identified in humans, is a syndrome of lower body adipose loss, leptin-deficient severe upper body adipose overgrowth, and insulin resistance caused by the p.Arg707Trp mutation in MFN2, encoding mitofusin 2. How the resulting selective form of mitochondrial dysfunctio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…However, these studies were not conducted with WAs in vivo and two comportments in the mitochondria. Recently, Mann reported that the p.Arg707Trp mutation in MFN2 caused severe upper body overgrowth and insulin resistance in humans and adipose‐specific mitochondrial abnormalities, but no apparent systemic metabolic disorder, in mice [32]. This result suggested that MFN2 is involved in regulating mitochondrial function in WA, however, its influence appear species‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were not conducted with WAs in vivo and two comportments in the mitochondria. Recently, Mann reported that the p.Arg707Trp mutation in MFN2 caused severe upper body overgrowth and insulin resistance in humans and adipose‐specific mitochondrial abnormalities, but no apparent systemic metabolic disorder, in mice [32]. This result suggested that MFN2 is involved in regulating mitochondrial function in WA, however, its influence appear species‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by weakness, numbness and pain in the distal regions of the body, CMT2A is often an early-onset progressively-worsening disease (8). In addition to peripheral neuropathy, patients with certain MFN2 variants can present with other pathogenic phenotypes, such as myopathy (9)(10)(11), optic atrophy, sensorineural hearing loss, ataxia (12), or multiple symmetric lipomatosis (MSL) (13)(14)(15). How and why different variants in MFN2 lead mechanistically to pathology is not fully understood, though it is likely not as simple as reduced mitochondrial fusion (16).…”
Section: Introductionmentioning
confidence: 99%